Theoretical Study of the Effect of Weather Conditions on Vehicle Aerodynamic Properties - Brúnó Péter; István Lakatos (Engineering Proceedings)
One of the most widely researched fields within the automotive industry is the effect vehicles place on the environment. To achieve a sustainable transport system, reducing the pollution of vehicles is an essential issue. The aim of this paper is to examine how weather conditions influence a vehicle’s operation. The study examines potential methods to evaluate the effect of different weather conditions on the aerodynamic parameters of a vehicle. Aerodynamic properties can be measured with the help of computational fluid dynamics (CFD), a wind tunnel and test-track measurements. On-board diagnostics are also examined to collect data on aerodynamics. These methods can monitor several parameters to measure and visualize the effects of weather conditions. The theoretical background to the related aerodynamic parameters is summarized.